Epidemiological profi le of leprosy in Guarulhos, SP - Edilson Ribeiro Romão; Alessandro Mendonça Mazzoni (Universidade de Santa Cruz do Sul, 2013)
Rationale and Objectives: Need for continuous monitoring to characterize the trend and magnitude of the disease, assessment of most affected population groups, consolidation of epidemiological surveillance and also as an indicator of the effi ciency of currently ongoing action and control programs. Thus, the aim of the study was to describe the epidemiology profi le of leprosy in the city of Guarulhos, from 2004 a 2009. Methods: A descriptive, cross sectional and retrospective study, with data collection in the years 2004-2009 obtained from the National Information System for Notifiable Diseases (SINAN), the Brazilian Institute of Geography and Statistics (IBGE) and the Unifi ed Health System Department of Informatics (DATASUL). Results: A total of 282 cases of leprosy were reported in the study period, resulting in a mean detection rate of 3.72 cases per 100,000 inhabitants/year. There was a predominance of cases in the male sex, Caucasians, age 20-39 years and schooling level between the 5th and 8th grade of Elementary school. Grade II disability was detected in 15.8% of cases and most patients were multibacillary, with the borderline and lepromatous clinical forms. Conclusion: Indicators of good care in relation to actions and care services after disability detection are in contrast with the peak proportion of patients that have been diagnosed with grade II disability and the high percentage of multibacillary cases. Thus, changes are necessary in the current control and surveillance programs, aiming to decrease disease dissemination. KEYWORDS Leprosy. Guarulhos. Epidemiology. Public Health.